Odpowiedź :
Odpowiedź:
a)
2/x = 3/(x - 1)
jesli masz takie dzialanie, nie zapomnij, ze zapisujesz je na krzyz
3x = 2(x - 1)
3x = 2x - 2
3x - 2x = -2
x = -2
b)
4/(x + 1) = 5/x
5(x + 1) = 4x
5x + 5 = 4x
5x - 4x = -5
x = -5
c)
3/5 = (2x - 1)/(2 - 5x)
3(2 - 5x) = 5(2x - 1)
6 - 15x = 10x - 5
-15x - 10x = -5 - 6
-25x = -11 /:(-25)
x = 11/25
d)
(2x + 1)/(1 - 2x) = 2/3
3(2x + 1) = 2(1 - 2x)
6x + 3 = 2 - 4x
6x + 4x = 2 - 3
10x = -1 /:10
x = -1/10
e)
(0,4x - 1)/3 = (2x - 5)/2
2(0,4x - 1) = 3(2x - 5)
0,8x - 2 = 6x - 15
0,8x - 6x = -15 + 2
-5,2x = -13 /:(-5,2)
x = 2,5
f)
(4 + x²)/x = (2x - 1)/2
2(4 + x²) = x(2x - 1)
8 + 2x² = 2x² - x
2x² - 2x² + x = -8
x = -8
Szczegółowe wyjaśnienie: